Study of the high resolution FTIR spectrum of CH2CD2 in the region of 1300-1450 cm−1: The ν12(A1) and 2ν10(A1) bands; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 161 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Beryozkin K. B. Kirill Borisovich; Sklyarova E. A. Elena Aleksandrovna; Maul C.; Gericke К. Н.; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann (2015, 2015)
Title screen